DYSTOCIA DUE TO ANOMALOUS FETUS IN A NON DESCRIPT DOE - JYOTHI, K; Reddy, Y V PRIDHVIDHAR (The Indian Journal of Animal Reproduction, 2022)
A dead male fetus with arthrogryposis and brachygnathism in ventrotransvers presentationand its pervaginaldelivery after partial fetotomyunder epidural anaesthesia, in a pleuriparous non descript goat was reported.
Keywords: Arthrogryposis; Brachygnathism; Ventrotransverse; Fetotomy